Penerapan Product Knowledge dan Strategi UpSelling Pada Chandra Tech Palembang - Fitri Purwaningtias (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
Chandra Tech store is a store that sells computer along with other computer accessories. In the Chandra store sales system is still having difficulties in searching for existing products and difficulties in finding information on goods products in the store and information specifications of goods to be purchased and still lack of public knowledge about the existence of this Chandra store. To overcome this problem then the application of product knowledge is suitable for this research is to provide information about the product to be sold with detail of goods, and recommends an up selling strategy in sales by explaining the most expensive products, product searches, and about purchases and payments as well as about purchases and payments that can be done so that customers become more interested in purchasing the most expensive products. The research is website for product selling with the application of product knowledge and sales up selling strategy with a descriptif method for research and system development method is OOAD (Object Oriented Analysis and Design) starting from requirements, analysis, design, implementation and testing. With this website can help customers in facilitating the purchase of products in this store and can help the store to promote products sold and can raise services to customers through online sales.